2020
DOI: 10.1007/s13238-020-00748-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota alterations are distinct for primary colorectal cancer and hepatocellular carcinoma

Abstract: Colorectal cancer (CRC) and hepatocellular carcinoma (HCC) are the second and third most common causes of death by cancer, respectively. The etiologies of the two cancers are either infectious insult or due to chronic use of alcohol, smoking, diet, obesity and diabetes. Pathological changes in the composition of the gut microbiota that lead to intestinal inflammation are a common factor for both HCC and CRC. However, the gut microbiota of the cancer patient evolves with disease pathogenesis in unique ways that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 95 publications
2
46
0
Order By: Relevance
“…Japanese research reported that L. pacaense was at high levels in healthy centenarians compared with IBD patients [39]. Another previous study indicated the genus Roseburia was found in higher abundance in healthy controls compared with CRC and hepatocellular carcinoma patients [40]. R. inulinivorans acts as a probiotic associated with mucus production and is signi cantly more abundant in healthy controls than in rectal cancer patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese research reported that L. pacaense was at high levels in healthy centenarians compared with IBD patients [39]. Another previous study indicated the genus Roseburia was found in higher abundance in healthy controls compared with CRC and hepatocellular carcinoma patients [40]. R. inulinivorans acts as a probiotic associated with mucus production and is signi cantly more abundant in healthy controls than in rectal cancer patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…The CRC is one of the most commonly diagnosed and fatal cancers worldwide [ 1 ]. Changes in diet habits and aging may lead to an increase in the incidence of CRC [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…3.6. JHD decreased the in ltration of in ammatory cells and inhibited the IL-6/STAT3 pathway in tumors following the modulation of GM Pathological changes in the composition of the GM that lead to intestinal in ammation are a common factor for HCC [19]. The GM can gain access to the liver as a result of a chronic in ammation disease associated to dysfunction of the intestinal barrier.…”
Section: Sorafenib Induced Increased Proin Ammatory Microbiotamentioning
confidence: 99%